Method for repairing glass made of organic material
Through cleaning and gradual polishing methods, combined with multiple polishing treatments, the problems of aging and poor light transmittance during repair of organic glass made of organic materials in the prior art are solved, and the effect of efficient repair and light transmittance is achieved.
Patent Information
- Application Number
- CN202510257865.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-05
- Publication Date
- 2025-04-25
AI Technical Summary
In the prior art, when repairing glass made of organic materials, chemical fumigation will accelerate glass aging, and ordinary grinding methods will lead to poor light transmission.
Cleaning is carried out with cleaning liquid, then gradually polishing is used with different mesh numbers of sandpaper, and scratches, aging surfaces and sand marks are removed through multiple polishing treatments, and finally restore the mirror effect.
It effectively repairs scratches and aging damage of organic glass made of glass, improves the light transmittance after repair, and avoids the problems of glass aging and reduced light transmittance.
Smart Images

Figure CN119871164A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of repairing glass made of organic materials, and in particular to a method for repairing glass made of organic materials. Background Art
[0002] Glass made of organic materials is made of polymer compounds, and scratches are very likely to appear on the surface, resulting in the breakage of the surface molecular chains, which increases the difficulty of repair. The repair of organic material glass can be carried out by chemical fumigation and ordinary grinding. The chemical fumigation method is not ideal for severely aged areas, especially for those with deep cracks. Since the chemical fumigation method destroys the internal molecular chains, it will accelerate the aging of organic material glass and cause problems such as rapid yellowing. Ordinary grinding methods generally use sandpaper for grinding, which can easily cause problems such as poor light transmittance of the treated glass. Summary of the invention
[0003] The embodiment of the present invention provides a method for repairing glass made of organic materials, which can at least solve some of the above technical problems existing in the prior art.
[0004] In a first aspect, an embodiment of the present invention provides a method for repairing glass made of organic materials, comprising:
[0005] Clean with cleaning fluid to remove surface stains;
[0006] Performing a first polishing process with a first abrasive to remove residual stains and an aged surface layer;
[0007] Use sandpaper of different meshes to polish in order from small to large meshes;
[0008] Performing a second polishing process with a second abrasive to remove sand marks formed by sandpaper polishing;
[0009] A third polishing process is performed using a third abrasive to remove glare lines.
[0010] In an optional embodiment, in the first polishing process, the polishing machine rotates at a speed of 1500-2000 rpm, a short wool disc is used as the polishing disk, and an angle of 15 degrees is maintained between the polishing disk and the glass surface.
[0011] In an optional embodiment, the first abrasive comprises the following components in percentage by mass:
[0012] Silicon carbide 9.70%-9.55%, aluminum oxide 11.20%-11.05%, silicon oxide 9.45%-9.30%, detergent 1.70%-2.10%, rust remover 1.90%-2.10%, lubricant 2.40%-2.55%, emulsifier 1.90%-2.10%, thickener 0.95%-1.10%, pH adjuster 0.45%-0.55%, and the balance is deionized water.
[0013] In an optional embodiment, sandpaper with different mesh sizes is used to perform grinding in order from small to large mesh sizes, including:
[0014] For deep scratches, use 600-grit water sandpaper to polish along the scratch lines;
[0015] Use 1500-grit sandpaper to fully cover the 600-grit sandpaper marks for polishing;
[0016] Use 2000 grit sandpaper to fully cover the 1500 grit sandpaper marks for sanding.
[0017] In an optional embodiment, when sanding with 1500-grit sandpaper and 2000-grit sandpaper, sanding is performed back and forth in the horizontal or vertical direction.
[0018] In an optional embodiment, the second abrasive comprises the following components in percentage by mass:
[0019] 16%-22% of abrasive particles, 1.00%-1.40% of rust remover, 1.25%-1.70% of lubricant, 1.00%-1.40% of emulsifier, 0.50%-0.70% of thickener, 0.25%-0.35% of pH regulator, and the balance is deionized water. The abrasive particles include silicon carbide and aluminum oxide.
[0020] In an optional embodiment, the mass percentages of the abrasive particles in the second abrasive are as follows: 8.75%-9.50% for silicon carbide and 10.50%-11.25% for aluminum oxide.
[0021] In an optional embodiment, in the second polishing process, an eccentric polishing machine is used, and a long wool disk is used as the polishing disk. During the polishing process, the applied pressure reduces the thickness of the long wool disk by 1 / 3, and a tic-tac-toe polishing track is used, with alternating horizontal and vertical polishing.
[0022] In an optional embodiment, the third abrasive comprises the following components in percentage by mass:
[0023] Silicon carbide 9.70%-10.30%, aluminum oxide 11.50%-12.00%, silicon oxide 9.50%-10.50%, rust remover 1.90%-2.10%, lubricant 2.40%-2.55%, emulsifier 1.90%-2.10%, thickener 0.95%-1.10%, pH adjuster 0.45%-0.55%, and the balance is deionized water.
[0024] In an optional embodiment, in the third polishing process, an 8-shaped polishing track is adopted, and during the polishing process, the glass surface temperature is controlled below 60°C.
[0025] An embodiment of the present invention has the following advantages or beneficial effects:
[0026] In the method for repairing glass made of organic materials in the embodiment of the present invention, cleaning is performed with a cleaning liquid to remove stains on the surface; a first polishing treatment is performed with a first abrasive to remove residual stains and an aged surface layer; sandpapers of different mesh sizes are used to grind in order from small to large mesh sizes; a second polishing treatment is performed with a second abrasive to remove sand marks formed by sandpaper grinding; a third polishing treatment is performed with a third abrasive to remove glare lines. The method of the embodiment of the present invention uses a combination of polishing and grinding to repair glass made of organic materials, and uses different abrasives to perform multiple polishing treatments on the glass made of organic materials, repairs scratches, aging and other damage on the surface of the glass made of organic materials, and improves the light transmittance after repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] The above and other features and advantages of the present invention will become more apparent by describing in detail exemplary embodiments thereof with reference to the attached drawings.
[0028] Figure 1 is a schematic flow chart of a method for repairing glass made of organic materials according to an exemplary embodiment;
[0029] Figure 2-Figure 6 These are pictures of the samples after the second polishing treatment in Example 1 and Comparative Examples 4-7. DETAILED DESCRIPTION
[0030] Example embodiments will now be described more fully with reference to the accompanying drawings. However, example embodiments can be implemented in a variety of forms and should not be construed as limited to the embodiments set forth herein; rather, these embodiments are provided so that the present invention will be comprehensive and complete and fully convey the concepts of the example embodiments to those skilled in the art. The same reference numerals in the figures represent the same or similar structures, and thus their detailed description will be omitted.
[0031] The terms "a", "an", "the", and "said" are used to indicate the presence of one or more elements / components / etc.; the terms "comprising" and "having" are used to express an open-ended inclusive meaning and mean that additional elements / components / etc. may be present in addition to the listed elements / components / etc.
[0032] See also Figure 1 The embodiment of the present invention provides a method for repairing glass made of organic materials, comprising:
[0033] Clean with cleaning fluid to remove surface stains;
[0034] Performing a first polishing process with a first abrasive to remove residual stains and an aged surface layer;
[0035] Use sandpaper of different meshes to polish in order from small to large meshes;
[0036] Performing a second polishing process with a second abrasive to remove sand marks formed by sandpaper polishing;
[0037] A third polishing process is performed using a third abrasive to remove glare lines.
[0038] In the method for repairing glass made of organic materials in the embodiment of the present invention, cleaning with a cleaning liquid can remove stains on the surface and prevent large dust particles on the surface from damaging the glass surface during subsequent processing. The first polishing treatment with the first abrasive can remove residual stains and aged surface layers. The stubborn stains and aged surface layers remaining after cleaning can be removed by the first polishing treatment, laying a foundation for subsequent repairs and preventing new damage caused by residual stubborn stains, aged surface layers, etc. when sandpaper is used. In the embodiment of the present invention, sandpaper with different mesh sizes is used to polish in order from small to large mesh sizes, so as to remove scratches on the surface and improve the smoothness of the surface. In the embodiment of the present invention, the second polishing treatment with the second abrasive can remove sand marks formed by sandpaper polishing, and the third polishing treatment with the third abrasive can remove glare lines and restore the mirror effect. The method of the embodiment of the present invention uses a combination of polishing and grinding to repair organic material glass, and uses different abrasives to polish the organic material glass multiple times to repair scratches, aging and other damage on the surface of the organic material glass, and improve the transmittance after repair.
[0039] In some embodiments, a special glass cleaning fluid made of organic material is used for comprehensive cleaning. Cleaning with the cleaning fluid can remove stains such as oil stains and dust, ensuring that no large dust particles will cause secondary scratches during subsequent processing.
[0040] When cleaning glass made of organic materials, it can be pre-cleaned first, and then cleaned by spraying cleaning liquid. Pre-cleaning can be rinsed with clean water. When spraying the cleaning liquid, it can be sprayed evenly from top to bottom, and wiped from left to right with a cleaning bear paw glove. Then rinse again. The rinsing order can be from top to bottom, moving in one direction. Make sure that the cleaning liquid is rinsed clean. In specific implementation, the cleaning liquid can use neutral nano-active factors, which can easily dissolve various stubborn stains and remove more than 90% of stains. The cleaning process can also use ultrasonic cleaning and other methods.
[0041] In some embodiments, in the first polishing process, the polishing machine rotates at a speed of 1500-2000 rpm, the polishing disc uses a short wool disc, and the polishing disc maintains an angle of 15 degrees with the glass surface. By using the first abrasive and the above-mentioned polishing process, stubborn stains, fine scratches and aged surface layers can be removed. The polishing machine can be a handheld polisher. Appropriate pressure is applied during the polishing process, and the polishing disc maintains an angle of 15 degrees with the glass surface, and the speed of 1500-2000 rpm is used to remove stubborn stains, fine scratches and aged surface layers.
[0042] In some embodiments, the first abrasive includes first abrasive particles and a cleaning agent, wherein the mass percentage of the first abrasive particles in the first abrasive may be 29.9%-30.3%, and the mass percentage of the cleaning agent may be 1.7%-2.1%. The combination of the first abrasive particles and the cleaning agent can effectively remove stubborn stains, slight scratches, and aged surfaces.
[0043] The first abrasive particles may include silicon carbide, aluminum oxide, and silicon oxide.
[0044] The first abrasive may further include appropriate amounts of a rust remover, a lubricant, an emulsifier, a thickener and a pH adjuster.
[0045] In some embodiments, the first abrasive includes the following components in mass percentage: silicon carbide 9.70%-9.55%, aluminum oxide 11.20%-11.05%, silicon oxide 9.45%-9.30%, detergent 1.70%-2.10%, rust remover 1.90%-2.10%, lubricant 2.40%-2.55%, emulsifier 1.90%-2.10%, thickener 0.95%-1.10%, pH regulator 0.45%-0.55%, and the balance is deionized water. In the embodiments of the present invention, the efficiency and effect of the first polishing process are taken into account through a reasonable formulation.
[0046] The particle size of silicon carbide and aluminum oxide can be 0.5-1um. Silicon carbide and aluminum oxide can be high-purity low-metal ion type, and the particle size of silicon carbide and aluminum oxide is uniform. The particle size of silicon oxide can be 30-80nm. Silicon oxide uses high-purity colloidal particles, the particles are spherical, the particle size is concentrated, and the particles are uniform.
[0047] When repairing glass made of organic materials, the first abrasive of the embodiment of the present invention can effectively remove stubborn stains, as well as slight scratches and aged surface layers without causing secondary damage to the glass.
[0048] The preparation process of the first abrasive may include the following steps: weighing each component in proportion; adding each component in a good proportion to deionized water using a high-speed disperser to fully blend and homogenize the raw materials to obtain a polishing emulsion. When adding each component, different temperatures and addition methods may be used according to the chemical and physical properties of each component.
[0049] In some embodiments, polishing with sandpaper of different meshes may include: when the glass surface has deep scratches, polishing the deep scratches with 600 mesh water sandpaper. Polishing with sandpaper of different meshes may also include polishing with 1500 mesh sandpaper and 2000 mesh sandpaper respectively. When the scratch depth on the glass surface is greater than the target value, the glass surface has deep scratches. The target value may range from 30μm to 80μm. The specific value of the target value may be 40μm, 50μm, 60μm, or 70μm. For example, when the glass surface has scratches with a depth greater than 30μm, it means that the glass surface has deep scratches, and the glass surface may be polished with 600 mesh water sandpaper.
[0050] When sanding with sandpaper of different grits, the sanding in the later order should completely cover the sand marks of the previous sanding.
[0051] In some embodiments, sandpaper with different mesh sizes is used to perform grinding in order from small to large mesh sizes, including:
[0052] For deep scratches, use 600-grit water sandpaper to polish along the scratch lines;
[0053] Use 1500-grit sandpaper to fully cover the 600-grit sandpaper marks for polishing;
[0054] Use 2000 grit sandpaper to fully cover the 1500 grit sandpaper marks for sanding.
[0055] Use 600-grit water sandpaper to sand along the scratch lines to remove deeper scratches. Use 1500-grit sandpaper and 2000-grit sandpaper to sand in sequence to eliminate the sandpaper marks formed by the previous sanding and improve the surface smoothness.
[0056] When using 600-grit water sandpaper for grinding, you can use manual grinding or polishing machine.
[0057] When grinding with 1500-grit sandpaper and 2000-grit sandpaper, you can use a polishing machine for grinding. For example, a polishing machine with a 6-8-inch sandpaper disc can be used with 1500-grit sandpaper and 2000-grit sandpaper for grinding.
[0058] In some embodiments, when sanding with 1500-grit sandpaper and 2000-grit sandpaper, sanding is performed back and forth in the horizontal or vertical direction. Compared with circular sanding, sanding back and forth in the horizontal or vertical direction can achieve a better sanding effect.
[0059] In some embodiments, the second abrasive includes the following components in percentage by weight:
[0060] Abrasive particles 16%-22%, rust remover 1.00%-1.40%, lubricant 1.25%-1.70%, emulsifier 1.00%-1.40%, thickener 0.50%-0.70%, pH adjuster 0.25%-0.35%, the balance is deionized water, the abrasive particles include silicon carbide and aluminum oxide. Polishing with the second abrasive can effectively remove sand marks and avoid forming obvious fiber marks on the glass surface.
[0061] In some embodiments, the mass percentage of the abrasive particles in the second abrasive is as follows: 8.75%-9.50% of silicon carbide and 10.50%-11.25% of aluminum oxide. By properly mixing silicon carbide and aluminum oxide, a better polishing effect and polishing efficiency can be achieved.
[0062] The particle size of silicon carbide and aluminum oxide can be 3.5-5 μm, and silicon carbide and aluminum oxide can be high-purity and low-metal ion type with uniform particle size.
[0063] The preparation process of the second abrasive may include the following steps: weighing each component in proportion; adding each component in proportion to deionized water using a high-speed disperser to fully blend and homogenize the raw materials to obtain a polishing emulsion. When adding each component, different temperatures and addition methods may be used according to the chemical and physical properties of each component.
[0064] In some embodiments, in the second polishing process, an eccentric polishing machine is used, and a long wool disk is used as the polishing disk. During the polishing process, the pressure applied reduces the thickness of the long wool disk by 1 / 3, and a tic-tac-toe polishing track is used, with alternating horizontal and vertical polishing.
[0065] In some embodiments, the third abrasive includes the following components in percentage by weight:
[0066] Silicon carbide 9.70%-10.30%, aluminum oxide 11.50%-12.00%, silicon oxide 9.50%-10.50%, rust remover 1.90%-2.10%, lubricant 2.40%-2.55%, emulsifier 1.90%-2.10%, thickener 0.95%-1.10%, pH adjuster 0.45%-0.55%, and the balance is deionized water. The third abrasive of the embodiment of the present invention can effectively remove residual polishing lines and glare lines, and can also avoid fiber marks caused by the polishing disk.
[0067] The particle size of silicon carbide and aluminum oxide can be 0.5-1um, silicon carbide and aluminum oxide can be high-purity low-metal ion type, and the particle size is uniform. The particle size of silicon oxide can be 30-80nm, silicon oxide can be high-purity colloidal particles, and its particles are spherical, the particle size is concentrated, and the particles are uniform.
[0068] The preparation process of the third abrasive may include the following steps: weighing each component in proportion; adding each component in proportion to deionized water using a high-speed disperser to fully blend and homogenize the raw materials to obtain a polishing emulsion. When adding each component, different temperatures and addition methods may be used according to the chemical and physical properties of each component.
[0069] In some embodiments, in the third polishing process, an 8-shaped polishing track is used, and during the polishing process, the glass surface temperature is controlled below 60°C.
[0070] In the embodiment of the present invention, the raw materials of each abrasive can be commercially available materials. In a specific implementation, the cleaning agent can be, for example, dioctyl sulfonated succinate sodium salt, the rust remover can be triethanolamine borate, the lubricant can be glycerol, the emulsifier can be polyacrylamide, the thickener can be amine oxide, and the pH adjuster can be sodium tripolyphosphate.
[0071] The material of the organic material glass in the embodiment of the present invention includes PMMA, PC, PETG and the like.
[0072] The following is a description of the embodiments of the present invention in conjunction with specific examples, comparative examples and related tests. The raw materials in the following embodiments and comparative examples are described as follows:
[0073] Silicon carbide, Shanghai Jinxindun Metal Materials Technology Co., Ltd., model: 500 nanometer silicon carbide 100G; 1 micron silicon carbide 1 kg; 3.5-5 micron silicon carbide 1 kg.
[0074] Alumina, Shanghai Jinxindun Metal Materials Technology Co., Ltd., model: 500 nanometer alumina 1 kg; 1 micron alumina 1 kg; 3.5-5 micron alumina 1 kg.
[0075] Silicon oxide, Hubei Huifu E-commerce Co., Ltd., model: HL-450, 10 kg, particle size 45 nm.
[0076] Sulfosuccinate dioctyl sodium salt, Shanghai Huijun Chemical Co., Ltd., model: OT-75.
[0077] Triethanolamine borate, Dexu New Materials (Guangzhou) Co., Ltd., model: DX621.
[0078] Glycerol, Shandong Defa Chemical Co., Ltd., model: Glycerol 011.
[0079] Polyacrylamide, Henan Saike Environmental Protection Technology Co., Ltd., model: ionic type, 25 kg.
[0080] Amine oxide, Zhengzhou Juepai Chemical Products Co., Ltd., model: LAO-30.
[0081] Sodium tripolyphosphate, Anhui Weimao Biotechnology Co., Ltd., model: STPP, 25 kg.
[0082] Example 1
[0083] The glass of the cableway cabin (PMMA, polymethyl methacrylate) used for more than 10 years is used as the substrate, and the substrate is cut into several pieces of the same size as samples.
[0084] Step 1: Cleaning
[0085] Rinse the sample surface with clean water, then spray the neutral nano active factor liquid evenly from top to bottom, then wipe it from left to right with the bear paw gloves for cleaning, and then rinse it. The rinsing order is from top to bottom, moving in one direction.
[0086] Step 2: First polishing process
[0087] 9.65% of silicon carbide, 11.15% of aluminum oxide, 9.40% of silicon oxide, 1.80% of detergent, 60.00% of deionized water, 2.00% of rust remover, 2.50% of lubricant, 2.00% of emulsifier, 1.00% of thickener and 0.50% of pH adjuster are weighed by mass percentage, and the weighed components are added to the deionized water by a high-speed disperser to fully blend and homogenize the raw materials to form a polishing emulsion, thereby obtaining a first polishing agent with a total mass of 1 kg, wherein silicon carbide adopts two particle sizes of 0.5um and 1um, and the mass ratio of the two particle sizes of silicon carbide is 1:1, the particle size of aluminum oxide is 1um, and the particle size of silicon oxide is 45nm.
[0088] The speed of the polishing machine is 1500-2000 rpm, and the polishing disc uses a short wool disc. When starting to polish, the polishing disc maintains a 15-degree angle with the glass surface. During the polishing process, appropriate downward pressure should be applied. The polishing time is 3 minutes.
[0089] Step 3: First polishing
[0090] For deep scratches, use a small diameter polisher with 600-grit water sandpaper to carefully grind along the scratch lines. Keep the force and direction consistent, not only to effectively remove the scratches, but also to make the extension range as small and smooth as possible.
[0091] Step 4: Second polishing
[0092] Use a polishing machine with a 6-8 inch sandpaper disc and 1500 grit sandpaper, and polish back and forth horizontally or vertically to fully cover the 600 grit sandpaper marks.
[0093] Step 5: Third polishing
[0094] Use a polishing machine with a 6-8 inch sandpaper disc and 2000 grit sandpaper, and polish back and forth horizontally or vertically to fully cover the 1500 grit sandpaper marks.
[0095] Step 6: Second polishing
[0096] 6.25% silicon carbide, 13.75% aluminum oxide, 75.00% deionized water, 1.25% rust remover, 1.56% lubricant, 1.25% emulsifier, 0.63% thickener and 0.31% pH regulator were weighed by mass percentage. The weighed components were added to the deionized water using a high-speed disperser to fully blend and homogenize the raw materials to form a polishing emulsion, and a second polishing agent with a total mass of 1 kg was obtained. The particle size of silicon carbide was 5 μm, and the particle size of aluminum oxide was 5 μm.
[0097] Use an eccentric polisher with a long wool disc to remove sandpaper marks and polishing marks left by the previous process. During the polishing process, add a small amount of the second abrasive each time, and add the second abrasive multiple times to avoid dry polishing. Polish for three minutes. During the polishing process, apply appropriate downward pressure to reduce the thickness of the long wool disc by 1 / 3. At this time, the contact area between the polishing disc and the glass is the largest and the efficiency is the highest. Use a tic-tac-toe polishing track, first horizontally and then vertically, and alternately polish horizontally and vertically several times to remove sand marks.
[0098] Step 7: Third polishing process
[0099] 10.25% of silicon carbide, 11.75% of aluminum oxide, 10% of silicon oxide, 60.00% of deionized water, 2.00% of rust remover, 2.50% of lubricant, 2.00% of emulsifier, 1.00% of thickener and 0.50% of pH adjuster are weighed by mass percentage. The weighed components are added to deionized water by a high-speed disperser to fully blend and homogenize the raw materials to form a polishing emulsion, and a third polishing agent with a total mass of 1 kg is obtained, wherein the particle size of silicon carbide is 1um, the particle size of aluminum oxide is 1um, and the particle size of silicon oxide is 45nm.
[0100] Use an eccentric polisher with a short wool disc and a third polishing agent to remove glare and fog to restore the mirror effect of the organic glass. During the polishing process, use an 8-shaped polishing track, first polishing in a horizontal 8-shaped pattern, then polishing in a vertical 8-shaped pattern, in order to remove glare. Polish for three minutes. During the polishing process, the glass surface temperature is controlled below 60°C to avoid excessive temperature that may cause surface gelatinization and capillary cracks.
[0101] Step 8. Check the surface condition of glass made of organic materials to see if there are any scratches, sand marks, glare marks, etc., and whether the light transmittance meets the standards.
[0102] Example 2
[0103] The difference from Example 1 is that in step 2, the particle size of silicon carbide is 0.5um, the particle size of aluminum oxide is 1um, and the particle size of silicon oxide is 45nm. In step 6, the second polishing agent is weighed to weigh 72.5g silicon carbide, 127.5g aluminum oxide, 750g deionized water, 12.5g rust remover, 15.6g lubricant, 12.5g emulsifier, 6.3g thickener, and 3.1g pH adjuster. The polishing time is 15 minutes.
[0104] Example 3
[0105] The difference from Example 1 is that in step 6, the second polishing agent is weighed to include 82.5 g of silicon carbide, 117.5 g of aluminum oxide, 750 g of deionized water, 12.5 g of rust remover, 15.6 g of lubricant, 12.5 g of emulsifier, 6.3 g of thickener, and 3.1 g of pH adjuster. The polishing time is 15 minutes.
[0106] Example 4
[0107] The difference from Example 1 is that in step 6, the second polishing agent is weighed to include 92.5 g of silicon carbide, 107.5 g of aluminum oxide, 750 g of deionized water, 12.5 g of rust remover, 15.6 g of lubricant, 12.5 g of emulsifier, 6.3 g of thickener, and 3.1 g of pH adjuster. The polishing time is 15 minutes.
[0108] Comparative Example 1
[0109] The difference from Example 1 is that in step 2, the first polishing agent is 10.00% silicon carbide, 11.50% aluminum oxide, 9.75% silicon oxide, 0.75% detergent, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener and 0.50% pH adjuster, to obtain a first polishing agent with a total mass of 1 kg.
[0110] Comparative Example 2
[0111] The difference from Example 1 is that in step 2, the first polishing agent is 9.90% silicon carbide, 11.40% aluminum oxide, 9.65% silicon oxide, 1.05% detergent, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a first polishing agent with a total mass of 1 kg.
[0112] Comparative Example 3
[0113] The difference from Example 1 is that in step 2, the first polishing agent is 9.75% silicon carbide, 11.25% aluminum oxide, 9.50% silicon oxide, 1.50% detergent, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a first polishing agent with a total mass of 1 kg.
[0114] Comparative Example 4
[0115] The difference from Example 1 is that in step six, the second polishing agent is 10.00% silicon carbide, 22.00% aluminum oxide, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a second polishing agent with a total mass of 1 kg.
[0116] Comparative Example 5
[0117] The difference from Example 1 is that in step six, the second polishing agent is 8.75% silicon carbide, 19.25% aluminum oxide, 65.00% deionized water, 1.75% rust remover, 2.19% lubricant, 1.75% emulsifier, 0.88% thickener, and 0.43% pH adjuster, to obtain a second polishing agent with a total mass of 1 kg.
[0118] Comparative Example 6
[0119] The difference from Example 1 is that in step six, the second polishing agent is 7.50% silicon carbide, 16.50% aluminum oxide, 70.00% deionized water, 1.50% rust remover, 1.88% lubricant, 1.50% emulsifier, 0.75% thickener, and 0.37% pH adjuster, to obtain a second polishing agent with a total mass of 1 kg.
[0120] Comparative Example 7
[0121] The difference from Example 1 is that in step six, the second polishing agent is 5.00% silicon carbide, 11.00% aluminum oxide, 80% deionized water, 1.00% rust remover, 1.25% lubricant, 1.00% emulsifier, 0.50% thickener, and 0.25% pH adjuster, to obtain a second polishing agent with a total mass of 1 kg.
[0122] Comparative Example 8
[0123] The difference from Example 1 is that in step seven, the third polishing agent is 9.25% silicon carbide, 10.75% aluminum oxide, 12% silicon oxide, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a third polishing agent with a total mass of 1 kg.
[0124] Comparative Example 9
[0125] The difference from Example 1 is that in step seven, the third polishing agent is 10.25% silicon carbide, 12.75% aluminum oxide, 9% silicon oxide, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a third polishing agent with a total mass of 1 kg.
[0126] Comparative Example 10
[0127] The difference from Example 1 is that in step seven, the third polishing agent is 11.25% silicon carbide, 13.75% aluminum oxide, 5% silicon oxide, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a third polishing agent with a total mass of 1 kg.
[0128] Comparative Example 11
[0129] The difference from Example 1 is that in step seven, the third polishing agent is 9.25% silicon carbide, 10.75% aluminum oxide, 12% polycrystalline diamond, 60.00% deionized water, 2.00% rust remover, 2.50% lubricant, 2.00% emulsifier, 1.00% thickener, and 0.50% pH adjuster, to obtain a third polishing agent with a total mass of 1 kg.
[0130] Comparative Example 12
[0131] The difference from Example 1 is that the first polishing process in step 2 is missing.
[0132] Comparative Example 13
[0133] The difference from Example 1 is that the second polishing process in step six is missing.
[0134] The samples obtained after the first polishing treatment in Example 1-2 and Comparative Example 1-3 were observed and compared.
[0135] Check whether there are any stains such as oil on the sample, and compare the changes with those before polishing. The changes are divided into 5 levels: very obvious, obvious, general, not obvious, and no change.
[0136] The comparison results are shown in Table 1 below.
[0137] Table 1
[0138]
[0139] The comparison results show that the comparison before and after the first polishing treatment of Example 1 and Example 2 is very obvious, the stubborn stains and oil stains have been completely removed, and no secondary damage is caused to the glass substrate. Comparative Examples 1-3 have obvious stains remaining after the first polishing treatment, and the first polishing effect is poor.
[0140] The samples after the second polishing treatment in Example 1 and Comparative Examples 4-7 were observed and compared, and the approximate number of fiber marks left on the samples was checked and rated: many, more, few, less, and none.
[0141] See also Figures 2 to 6 , Figures 2 to 5 They are the samples after the second polishing treatment of Comparative Examples 4-7, Figure 6 This is the sample after the second polishing treatment of Example 1.
[0142] The comparison results are shown in Table 2 below.
[0143] Table 2
[0144] model Comparative Example 4 Comparative Example 5 Comparative Example 6 Comparative Example 7 Example 1 Fiber Mark Rating many More few none none
[0145] According to the comparative test results, the samples of comparative examples 4-6 have obvious fiber marks, and although no obvious fiber marks were found in comparative example 7, there were sand marks that were not completely removed. Example 1 had the best effect, not only effectively removing the sand marks, but also no obvious fiber marks were observed.
[0146] The thickness of the sample after the second polishing treatment in Example 2-4 was measured by a thickness gauge before and after grinding. The measurement results are shown in Table 3.
[0147] Table 3
[0148] model Example 2 Example 3 Example 4 Thickness before grinding 3892.14um 3890.18um 3890.20um Thickness after grinding 3892.13um 3890.17um 3890.17um Difference (cutting amount) 0.01um 0.01um 0.03um
[0149] The comparative test results show that the sand marks on the samples of Examples 2-4 are basically removed. In addition, Example 4 does not leave long wool disc fiber marks, and the thickness value is the smallest, indicating that this formula has the strongest cutting force.
[0150] The light transmittance of the samples after the third polishing treatment in Example 1 and Comparative Examples 8-11 was measured using a light transmittance meter. The measurement results are shown in Table 4.
[0151] Table 4
[0152] model Example 1 Comparative Example 8 Comparative Example 9 Comparative Example 10 Comparative Example 11 Before polishing 70 69 69 69 70 After polishing 90 83 85 80 77
[0153] The comparative test results show that the sample obtained by processing in Example 1 not only achieves a mirror effect, but also has the best light transmittance.
[0154] By comparing the samples repaired in Example 1 with those in Comparative Example 12, it can be seen that due to the lack of the first polishing treatment, the sample polished by sandpaper in Comparative Example 12 has more scratches on the surface than the sample polished by sandpaper in Example 1. The subsequent second polishing treatment and the third polishing treatment have poor effects on removing the newly generated scratches.
[0155] By comparing the samples repaired in Example 1 with those in Comparative Example 13, it can be seen that due to the lack of the second polishing treatment, the sand marks on the surface of the sample in Comparative Example 13 after the third polishing treatment are not completely removed compared to the sample in Example 1 after the third polishing treatment.
[0156] In the embodiments of the present invention, the term "plurality" refers to two or more than two, unless otherwise clearly defined. The terms "installation", "connection", "fixation" and the like should be understood in a broad sense. For example, "connection" can be a fixed connection, a detachable connection, or an integral connection. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present invention can be understood according to specific circumstances.
[0157] In the description of the embodiments of the present invention, it needs to be understood that the directions or positional relationships indicated by the terms "upper" and "lower" are based on the directions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the embodiments of the present invention and simplifying the description, rather than indicating or implying that the device or unit referred to must have a specific direction, be constructed and operated in a specific orientation. Therefore, it cannot be understood as a limitation on the embodiments of the present invention.
[0158] In the description of this specification, the description of the terms "one embodiment", "a preferred embodiment", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the embodiment of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0159] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and changes. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for repairing glass made of organic materials, characterized in that: include: Clean with cleaning fluid to remove surface stains; Performing a first polishing process with a first abrasive to remove residual stains and an aged surface layer; Use sandpaper of different meshes to polish in order from small to large meshes; Performing a second polishing process with a second abrasive to remove sand marks formed by sandpaper polishing; A third polishing process is performed using a third abrasive to remove glare lines.
2. The method for repairing glass made of organic materials according to claim 1, characterized in that: In the first polishing process, the polishing machine rotates at a speed of 1500-2000 rpm, a short wool disc is used as the polishing disc, and an angle of 15 degrees is maintained between the polishing disc and the glass surface.
3. The method for repairing glass made of organic materials according to claim 1, characterized in that: The first abrasive comprises the following components in percentage by mass: Silicon carbide 9.70%-9.55%, aluminum oxide 11.20%-11.05%, silicon oxide 9.45%-9.30%, detergent 1.70%-2.10%, rust remover 1.90%-2.10%, lubricant 2.40%-2.55%, emulsifier 1.90%-2.10%, thickener 0.95%-1.10%, pH adjuster 0.45%-0.55%, and the balance is deionized water; the particle sizes of the silicon carbide and the aluminum oxide are 0.5-1um respectively, and the particle size of the silicon oxide is 30-80nm.
4. The method for repairing glass made of organic materials according to claim 1, characterized in that: Use sandpaper of different meshes to polish in order from small to large meshes, including: For deep scratches, use 600-grit water sandpaper to polish along the scratch lines; Use 1500-grit sandpaper to fully cover the 600-grit sandpaper marks for polishing; Use 2000 grit sandpaper to fully cover the 1500 grit sandpaper marks for sanding.
5. The method for repairing glass made of organic materials according to claim 4, characterized in that: When sanding with 1500-grit and 2000-grit sandpaper, sand back and forth horizontally or vertically.
6. The method for repairing glass made of organic materials according to claim 1, characterized in that: The second abrasive comprises the following components in percentage by mass: 16%-22% of abrasive particles, 1.00%-1.40% of rust remover, 1.25%-1.70% of lubricant, 1.00%-1.40% of emulsifier, 0.50%-0.70% of thickener, 0.25%-0.35% of pH regulator, and the balance is deionized water. The abrasive particles include silicon carbide and aluminum oxide.
7. The method for repairing glass made of organic material according to claim 6, characterized in that: The mass percentages of the abrasive particles in the second abrasive are as follows: 8.75%-9.50% for silicon carbide and 10.50%-11.25% for aluminum oxide; the particle sizes of the silicon carbide and aluminum oxide are 3.5-5 um, respectively.
8. The method for repairing glass made of organic materials according to claim 1, characterized in that: In the second polishing process, an eccentric polishing machine is used, and a long wool disk is used as the polishing disk. During the polishing process, the pressure applied reduces the thickness of the long wool disk by 1 / 3, and a tic-tac-toe polishing track is used, with alternating horizontal and vertical polishing.
9. The method for repairing glass made of organic materials according to claim 1, characterized in that: The third abrasive comprises the following components in percentage by mass: Silicon carbide 9.70%-10.30%, aluminum oxide 11.50%-12.00%, silicon oxide 9.50%-10.50%, rust remover 1.90%-2.10%, lubricant 2.40%-2.55%, emulsifier 1.90%-2.10%, thickener 0.95%-1.10%, pH adjuster 0.45%-0.55%, and the balance is deionized water; the particle sizes of the silicon carbide and the aluminum oxide are 0.5-1um respectively, and the particle size of the silicon oxide is 30-80nm.
10. The method for repairing glass made of organic materials according to claim 1, characterized in that: In the third polishing process, an 8-shaped polishing track is adopted, and during the polishing process, the glass surface temperature is controlled below 60°C.